(untitled) (Indian Journal of Animal Production and Management, 2014)
A survey on a study on feeding and breeding management practices adopted by sheep farmers in Telangana region of Andhra Pradesh was carried out with a sample size of 576 farmers across three zones by using multistage stratified random sampling technique. The survey revealed that farmers of these three zones mainly depend on grazing under extensive system to rear their flocks and the mean grazing time (hrs) and distance (km) in summer was 7.80 ± 0.04 and 6.00 ± 0.04 whereas mean grazing time (hrs) and distance other than summer months was 5.29 ± 0.05 and 3.76 ± 0.03, respectively. A Significant (P<0.01) association was observed between ram to ewe ratio among zones. Majority of the sheep famers (81.25%) reported that most of the sheep came into heat during autumn season followed by spring (13.84%) and summer seasons (4.86). Majority (82.47%) of sheep farmers harvested one lamb crop in a year.